THU0423 Time To Rebound in Joint Symptoms Following Discontinuation of TNFI Therapy after Achieving Low Disease Activity or Remission in Psoriatic Arthritis Patients Enrolled in The US Corrona Registry. (15th July 2016) - Harrold, L.R.; Stolshek, B.; Rebello, S.; Collier, D.; Mutebi, A.; Wade, S.W.; Malley, W.; Greenberg, J.D.; Etzel, C.J.
Abstract : Background: The treatment goal for patients (pts) with psoriatic arthritis (PsA) is to suppress disease activity. Little is known about clinical outcomes in pts who stop TNFi therapy after achieving low disease activity (LDA) during routine care. Objectives: We evaluated time to rebound (i.e., increase in joint symptoms after therapy discontinuation) in pts with PsA who achieved LDA prior to stopping TNFi therapy as well as changes in measures of disease activity at the first visit following TNFi discontinuation. Methods: In the Corrona registry, we identified pts with PsA who initiated a TNFi (adalimumab, etanercept, infliximab, golimumab), achieved LDA based on Clinical Disease Activity Index (CDAI) ≤10 on TNFi therapy, discontinued TNFi altogether while still in LDA (persistence on conventional disease modifying medication was allowed) and had at least 1 follow-up visit while off TNFi. Demographic and clinical characteristics were assessed at discontinuation date (index date). To assess time to rebound, pts were followed until earliest of the following events: rebound of symptoms (CDAI >10), initiation of another biologic/small molecule or last follow-up visit. Kaplan-Meier curves were generated for time to rebound (CDAI >10). To assess impact of TNFi discontinuation, change in disease activity measures including CDAI, modified Health Assessment Questionnaire (mHAQ), pt and physician global assessments, and pt pain were assessed between discontinuation and first post-index visit. Results: There were 94 pts (57% female, 51% biologic-experienced at TNFi initiation) who met study criteria. At TNFi discontinuation, mean (standard deviation [SD]) age and disease duration were 52.6 (12.7) and 9.8 (7.4) years, respectively. Over time, 67 (73%) pts had a rebound in symptoms, with median time to rebound of 8 months (95% CI 6–12). At first post-index visit, there was a significant mean increase in all measures of disease activity except mHAQ (Table). Conclusions: Rebound of symptoms in PsA patients occurred frequently with the majority of patients having worsening of disease activity by the next visit after TNFi discontinuation. These results suggest careful consideration before stopping these agents after achievement of low disease activity. Acknowledgement: This study is sponsored by Corrona, LLC. The Corrona RA registry has been supported through contracted subscriptions in the last two years by AbbVie, Amgen, BMS, Crescendo, Genentech, Horizon Pharma USA, Janssen, Eli Lilly, Novartis, Pfizer, and UCB. Disclosure of Interest: L. Harrold Grant/research support from: Pfizer and Astra Zeneca, Consultant for: Genentech and Pfizer, Employee of: Corrona, LLC, B. Stolshek Shareholder of: Amgen, Inc., Employee of: Amgen, Inc., S. Rebello Employee of: Corrona, LLC, D. Collier Shareholder of: Amgen, Inc., Employee of: Amgen, Inc., A. Mutebi Employee of: Amgen, Inc., S. Wade Consultant for: Amgen, Inc., W. Malley Employee of: Corrona, LLC, Paid instructor for: Lamar University, J. Greenberg Shareholder of: Corrona, LLC, Consultant for: AstraZeneca, Celgene, Genentech, Janssen, Novartis and Pfizer, Employee of: Corrona, LLC, C. Etzel Consultant for: Merck, Employee of: Corrona, LLC